Capacity Choice and Allocation: Strategic Behavior and Supply Chain Performance - Cachon, Gérard P.; Lariviere, Martin A. (Management Science, 1999)
We consider a simple supply chain in which a single supplier sells to several downstream retailers. The supplier has limited capacity, and retailers are privately informed of their optimal stocking levels. If retailer orders exceed available capacity, the supplier allocates capacity using a publicly known allocation mechanism, a mapping from retailer orders to capacity assignments. We show that a broad class of mechanisms are prone to manipulation: Retailers will order more than they need to gain a more favorable allocation. Another class of mechanisms induces the retailers to order exactly their needs, thereby revealing their private information. However, there does not exist a truth-inducing mechanism that maximizes total retailer profits. We also consider the supplier's capacity choice. We show that a manipulable mechanism may lead the supplier to choose a higher level of capacity than she would under a truth-inducing mechanism. Nevertheless, her choice will appear excessively restrictive relative to the prevailing distribution of orders. Furthermore, switching to a truth-inducing mechanism can lower profits for the supplier, the supply chain, and even her retailers. Hence, truth-telling is not a universally desirable goal.